THE EFFECT OF INTERNAL AND EXTERNAL FACTORS ON ENTREPRENEURIAL INTEREST MEDIATED BY ENTREPRENEURSHIP EDUCATION ON STUDENTS OF AN NAJIYAH VOCATIONAL SCHOOL TANGGERANG OF 2019/2020 ACADEMIC YEAR - Siswiandini, Tyas (Dinasti International Journal of Digital Business Management, 2020)
Unemployment in Indonesia continues to increase every year. One cause of the unemployment problem is school graduates who have the goal of finding jobs, not developing more jobs. One step in reducing unemployment and increasing employment is by entrepreneurship through entrepreneurship education. An Najiyah Tangerang Vocational School is one of the schools that provide the entrepreneurial understanding and hands-on learning practice. This study aims to determine the effect of internal and external factors on entrepreneurial interest mediated by entrepreneurship education on students of An Najiyah Vocational School Tangerang. This study used a quantitative approach with data analysis in testing the measurement model and the structural model using SmartPLS software version 3.2.8. The results showed that internal and external factors had a significant positive effect on entrepreneurship education and entrepreneurial interest on students of An Najiyah Vocational School. If the internal and external factors were mediated by the variable of entrepreneurship education, the effect was significant on entrepreneurial interest. In addition, entrepreneurship education also has a significant positive effect on the entrepreneurial interest of An Najiyah Vocational School.